“Like King and Queen, Like Balinese and Sasak”: Musical Narratives at the Lingsar Temple Festival in Lombok, Indonesia - Harnish, David (Ethnologies, 2001)
The Lingsar temple pujawali, a primarily religious festival on the island of Lombok in Indonesia, conjoins Hindu Balinese migrants and local Muslim Sasak to worship together for rain and spring water, fertility, bountiful harvests, and cures and boons. This article explores the narrative elements of the presented music at the festival, and posits that performances, which structure and frame the event and its internal rites, are embodied narratives linked to myths, fertility, and moral orders. The performing arts at Lingsar also erect ethnicity and unify together the respective groups of Balinese and Sasak. This union, referred to as “like king and queen,” is generated through music and dance performance in conjunction with the rites of priests and the collective actions of participants.